Axiopsychological Differences of Men’s and Women’s Gender Displays in Modern Ukraine - Hulias, Inesa; Karpenko, Zinoviia (Journal of Education Culture and Society, 2022)
The study aim was to explain the axiopsychological differences in young men’s and women’s gender displays in modern Ukraine.Methods. The methods for theoretical analysis, synthesis and conceptual modelling of an individual’s life processes in the axiological dimension were used. The sample for the empirical study covered 300 students aged 17 - 22 years and 12 psychological examining techniques were used; the obtained data were subjected to one-way analysis of variance.Results. Significant statistical differences were found for 22 compared characteristics, symmetrically distributed between males (110 people) and females (190 people). We has found that the quantitative balance of axiopsychological gender priorities does not mean their semantic similarity: the polarization of respondents’ gender displays was recorded; in particular, women’s self-presentation focused on the top-teleological (absolute subject) level of life (expression of spiritual values ​​and goals), and men’ self-presentation focused on the mono-subject (causal-instrumental, individualistic-pragmatic) level. The study highlights the issues of ensuring the real gender equality in Ukraine by building a meritocratic society.Conclusions. The article presents the axiopsychological approach in personology and gender psychology and reveals corresponding operations to form an applied (psychological examining) model, which allowed us to obtain relevant scientific results about significant differences between Ukrainian men’s and women’s gender displays.